EVALUATION OF RESPONSE CORELLATION USING CHEMOMETRICS ANALYSIS FOR PRE-OPTIMIZATION QUERCETIN – SELF EMULSION FORMULATION - Shaum Shiyan; Jessica Nathasia; Galih Pratiwi (Universitas Muhammadiyah Magelang, 2022)
The optimization approach using the simplex lattice design (SCD) has many advantages, including a minimized number of experiments and a good description of the interactions between components. However, modeling with the SCD approach has not evaluated between responses. Therefore, this study aims to apply chemometric analysis to evaluate the response from the optimization stage using the quercetin – self emulsion formulations (quercetin-SEFs) as a model. SEFs were prepared using grapeseed oil, croduret, and PEG 400. The evaluated responses included emulsification time and transmittance. Both responses were developed in endurance test by centrifugation method and stability test using freeze-thaw. Chemometric analysis on CA produced a dendrogram, while PCA produced score plots, loading plots, scree plots, and biplots. Emulsification time has a positive correlation with transmittance value. The quercetin-SEFs formula in SCD was classified into three groups based on the similarity of characters. Chemometric analysis was successfully applied in evaluating the response to the quercetin-SEFs optimization modeling.